2004
DOI: 10.1111/j.1749-7345.2004.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Phosphorus Levels on Growth, Body Composition, Muscle and Bone Mineral Concentrations for Orange‐Spotted Grouper Epinephelus coioides Reared in Floating Cages

Abstract: A feeding experiment was conducted in floating cages (1.5 ± 1.0 ± 2.0 m) to determine the requirement of dietary phosphorus by juvenile orange‐spotted grouper Epinephelus coicodes. Five isonitrogenous (approximately 54% CP) fishmeal‐casein‐based diets that contained 0.68, 0.77, 0.86, 1.02 and 1.21% total phosphorus from ingredients and supplemental monocalcium phosphate (MCP: 0, 0.75,1.51,2.26,3.02%) were fed to the fish previously fed a basal diet (0.68% total phosphorus) for 2 wk. Fish were fed in triplicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 35 publications
2
13
0
1
Order By: Relevance
“…A high phosphorus diet may chelate zinc and other trace elements and reduce their absorption and metabolism in fish (Lall 2002;Vielma et al 2002), which resulted in reduced growth. In the present study, based on the second-order polynomial regression analysis of SGR against dietary phosphorus level, optimal dietary total phosphorus requirement for maximum growth performance was determined to be 0.89%, which was higher than those reported in several fish species, such as sunshine bass (0.41%, Brown et al 1993), mirror carp (0.67%, Kim et al 1998), European whitefish (0.62%; Vielma et al 2002), haddock (0.72%, Roy and Lall 2003), Japanese flounder (0.45-0.51%, Wang et al 2005), Japanese seabass (0.70%, Zhang et al 2006) and large yellow croaker (0.68%; Mai et al 2006), but relatively close to the requirement for Atlantic salmon (0.9%, Asgard and Shearer 1997), cobia (0.86%, Zhou et al 2004). The difference is probably due to a number of factors, including fish species, form of phosphorus (particularly relating to solubility), fish size, Values are mean ± SD of three replicates, and values within the same row with different letters are significantly different at P \ 0.05; CF (condition factor) = 100 9 (live weight, g)/(body length, cm) 3 ; VSI (viscerosomatic index) = 100 9 (viscera weight)/(body weight); HSI (hepatosomatic index) = liver weight 9 100/body weight Fig.…”
Section: Discussionmentioning
confidence: 87%
“…A high phosphorus diet may chelate zinc and other trace elements and reduce their absorption and metabolism in fish (Lall 2002;Vielma et al 2002), which resulted in reduced growth. In the present study, based on the second-order polynomial regression analysis of SGR against dietary phosphorus level, optimal dietary total phosphorus requirement for maximum growth performance was determined to be 0.89%, which was higher than those reported in several fish species, such as sunshine bass (0.41%, Brown et al 1993), mirror carp (0.67%, Kim et al 1998), European whitefish (0.62%; Vielma et al 2002), haddock (0.72%, Roy and Lall 2003), Japanese flounder (0.45-0.51%, Wang et al 2005), Japanese seabass (0.70%, Zhang et al 2006) and large yellow croaker (0.68%; Mai et al 2006), but relatively close to the requirement for Atlantic salmon (0.9%, Asgard and Shearer 1997), cobia (0.86%, Zhou et al 2004). The difference is probably due to a number of factors, including fish species, form of phosphorus (particularly relating to solubility), fish size, Values are mean ± SD of three replicates, and values within the same row with different letters are significantly different at P \ 0.05; CF (condition factor) = 100 9 (live weight, g)/(body length, cm) 3 ; VSI (viscerosomatic index) = 100 9 (viscera weight)/(body weight); HSI (hepatosomatic index) = liver weight 9 100/body weight Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The Orange-spotted Grouper Epinephelus coioides is a popular aquaculture species with a high market value in China, and the development of a commercial diet for this species is necessary. To date, some nutrient requirements have been investigated (Zhou et al 2004;Luo et al 2005Luo et al , 2006Luo et al , 2008Ye et al 2006Ye et al , 2007. Luo et al (2004a) reported that the optimum level of dietary protein for Orange-spotted Grouper juveniles is estimated to be 48%.…”
mentioning
confidence: 99%
“…Zinc content in the operculum of fish from T 5 group was significantly higher than all other treatments. Tissue zinc concentration was found to decrease at higher levels of dietary phosphorus in some of the previous studies (Vielma and Lall 1998a;Roy and Lall 2003;Zhou et al 2004). Yang et al (2006) found no variation in zinc concentration due to the variations in dietary phosphorus levels.…”
Section: Discussionmentioning
confidence: 67%
“…In some of the previous studies, bone iron concentration decreased significantly with increase in dietary phosphorus concentrations (Roy and Lall 2003). Conversely, some authors have reported that bone iron concentration increased with an increase in dietary phosphorus concentration (Zhou et al 2004;Helland et al 2005).…”
Section: Discussionmentioning
confidence: 85%